Odpowiedzi

Najlepsza Odpowiedź!
2010-03-05T15:41:47+01:00
A1,a2,a3 - ciąg arytmetyczny , zatem mamy
a1 + (a1+r) +(a1 +2r) = 21
3 a1 + 3 r = 21
a1 + r = 7 ---> r = 7 - a1
b1 = a1 -1
b2 = a2 -4 = a1 +r -4 = a1 +(7 -a1) - 4 = 3
b3 = a3 - 3 = a1 +2r - 3 = a1 +2*(7 - a1) - 3 = -a1 + 11
b1,b2,b3 - ciąg geometryczny , zatem
b2/b1 = b3 / b2
3/(a1-1) = (-a1 +11) / 3
(a1 -1)*(-a1 +11) = 3*3 = 9
-(a1)² +11 a1 + a1 - 11 = 9
-(a1)² + 12 a1 - 20 = 0
(a1)² - 12 a1 + 20 = 0
Δ =(-12)² -4*1*20 = 144 - 80 = 64
√Δ = 8
a1 = [12 - 8]/2 = 4/2 = 2 lub a1 = [12+ 8] /2 = 20/2 = 10
zatem r = 7 - a1 = 7 - 2 = 5 lub r = 7 - a1 = 7 - 10 = -3
I Przypadek - dla a1 = 2 oraz r = 5
mamy
a1 = 2, a2 = 2+5 = 7, a3 = 7+5 = 12
spr. 2 + 7 + 12 = 21
II Przypadek - dla a1 = 10 oraz r = -3
mamy
a1 = 10, a2 = 10 -3 = 7, a3 = 7 -3 = 4
spr. 10 + 7 + 4 = 21
Odp. Te liczby to: 2,7,12 lub 10,7,4.

24 4 24